Assuring Business School Learning With Games. (April 2016) - Wolfe, Joseph
Background. The Association to Advance Collegiate Schools of Business (AACSB ) has stated thatbusiness games can and should be used for business schoolAssurance of Learning (AoL) programs. There is no direct objective evidence that business games are valid for such applications. Aim. The purpose of the study presented in this article was to examine the extent to which a business game could be used for such applications. Method. Thevalidity of THE GLOBAL BUSINESS GAME was examined by assessing the degree to which it was available, accessed, used, engaged in and otherwise demonstratedinternal validity in a large European university program. Results. The recorded data for the game revealed that many of its enrolledplayers either did not directly engage in the experience, or were only minimally involved. Those who werecompletely engaged in the experience obtained superioreconomic results and created strategies and implementations that were rational, goal-oriented and correct for the simulation's modeled competitive environment. Conclusions. A large-scale business game can serve as an assurance of learning device, but it is only an incomplete evaluator due to subjectnon-involvement . Recommendations. Game publishers that state their games are valid for assurance of learning purposes should presentobjective evidence of their validity claims. Those engaged in assurance of learning programs should employ other methods for measuringoutcomes than those used in this study. Those using business games should take measures to insure their participants are engaged and are accountable within its teaching structure.